The Corrosion Erossion of Ship Propeller Al 7075 Produced by Gravity Sand Casting - Milka Rante; Muhammad Syahid; Onny Sutresman (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2019)
Propeller is one of the important components of ships and boats that function as motor or boat propulsion. The mechanical properties required in propeller material are high toughness, easy to cast, and good engine capability, as well as good resistance to corrosion and erosion. One of the aluminum alloys that have been widely used in major vessels in propeller systems is the Nickel-aluminum-bronze (NAB) alloy because it has an excellent combination of mechanical properties and corrosion-erosion resistance. Another type of aluminum alloy that is widely used as a machining component is the Al 7075 T651 because it has the highest strength among other aluminum alloys. The mechanical properties of the Al 7075 T651 are directly proportional to the erosion resistance of the propeller which agrees with the pot tester porridge. The higher the value of the erosion propeller failure that occurs also increases with increasing testing rotational speed. For corrosion, a propeller with air testing media at a speed of 1000 rpm which results in significant corrosion products. Keywords: Al 7075 T651, Slurry Pot Tester, Corrosion Erosion